Ilex paraguariensis supplementation may be an effective nutritional approach to modulate oxidative stress during perimenopause - Pereira, Ariana Aparecida Ferreira (2017)
Perimenopause is a period in a woman´s life that precedes menopause and is characterized by hormonal changes that result in increased oxidative stress. Since oxidative stress is associated with age-related diseases and perimenopausal symptoms including somato-vegetative manifestations, nutritional antioxidant supplementation may be an effective approach to minimizing this stress. Mate tea (MT) (Ilex paraguariensis), a typical and inexpensive beverage consumed in the Brazilian south-east, Argentina and Uruguay, increases antioxidant defense. We hypothesized that MT could minimize oxidative stress during perimenopause by modulating enzymatic antioxidant defense. To test this, we analyzed the lipid oxidative damage and antioxidant defense in erythrocytes and liver of rats, after MT treatment. Female Wistar rats (aged 16 months) in proven perimenopause period received 20 mg/kg BW/day of mate tea, by gavage (PM + MT group) or water (PM group). Female rats aged 4 months (AD group) received water. Erythrocytes and liver were used to determine lipid oxidative damage, determined by malondialdehyde (MDA); superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) activities. Total plasma antioxidant capacity was examined by ferric reducing antioxidant power assay (FRAP) and estrogen by radioimmunoassay. MT increased FRAP and did not change estrogen levels. Increased SOD and GPx, and reduced MDA were observed in both tissues studied. Increased CAT activity was observed only in the liver. We confirmed the hypothesis that MT was capable of minimizing oxidative stress in this period of life by modulating antioxidant defense.